Engineering foresight enhancing research and development capacity in the engineering fraternity - Abang Ali, Abang Abdullah (2001)
The lure towards professional practice amongst engineers and the absence of nationally funded engineering research institutes have taken a toll on the national capacity to undertake research in engineering in the country. University researchers have over the years been leaving in relatively large numbers for the more lucrative manufacturing and construction sectors in search of greener pastures and the universities are left with a never-ending task of recruiting and training new academic staff. Research institutes that had been established and fUnded by the government are predominantly in the agricultural sector and when calls were made to set up engineering research institutes, It happened during a lime when the government has developed reluctance in setting up new research institutes. While we hear calls for warld-class research, leading to Noble Laureates and extensive patenting and commercialization, we find engineering researchers hard-pressed to maintain a respectable level of R&D activities, let alone compete at the international level. Engineering research is expensive, given the cast of acquiring any state-of-the-art laboratory facilities required and unless there is a concerted effort to develop the engineering research infrastructure and human resource in the country, we may well continue to lag behind the more advanced countries in this stiffly competitive arena. An engineering foresight study is proposed to chart the way for engineering research in the country.